Information Visualizations and the Interpellation of a Social Subject - Drucker, Johanna (InfoDesign, 2022)
Though rarely used in critical discussion of information visualizations, theories of enunciation created in the context of linguistics and media theory offer an insight into the way graphic displays create and interpellate social subjects. The argument made here is that while the graphic conventions used for the display of information create the appearance of neutral statements, they are actually structured as modes of address. Critical tools can expose the power relations structured into visualizations and address the ways in which a social subject is specifically produced and positioned) within cultural systems. In addition, using the familiar maps of Covid outbreaks as an example, this discussion points to the various ways in which human experience, individual and collective, is erased from view, even as the scale of tragedy and suffering increases. This piece calls for a new critical understanding of the relations between subject production and graphical conventions as a way to read information visualizations and also infuse them with affective force that registers the human dimensions of data.